Kolaborasi Personil Sekolah dalam Pelaksanaan Bimbingan dan Konseling di Era Kurikulum Merdeka - Fitri, Maulida; F, Firman; S, Neviyarni (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Collaboration between school personnel is very important in implementing BK management. However, in reality the phenomenon seen in the field is that there are still school personnel who have not carried out their respective roles in providing guidance and counseling services to the maximum. Such as inadequate support for facilities and infrastructure from the school principal, guidance and counseling teachers who do not create programs effectively and efficiently, and subject/class teachers who do not cooperate in sharing information regarding student development patterns in class. In the implementation of management in schools, it is compiled by a curriculum called the independent curriculum. The Merdeka Curriculum emphasizes developing students' individual potential through a more flexible and personalized approach. In this context, the role of guidance and counseling becomes very important to help students overcome various academic and non-academic challenges. Therefore, efforts are needed to increase collaboration between school personnel in BK. So a good management system is needed so that BK services are carried out optimally. Therefore, the aim of this research is to examine in depth how guidance and counseling management works in optimizing the role of school personnel for collaborative implementation of guidance and counseling in schools. The method used in this research is a literature study by collecting data from previous research results and relevant results. The research results show that in implementing BK in schools, POAC must be implemented so that school personnel know and carry out their roles, in this way collaboration between school personnel can be created in implementing optimal BK in accordance with the Merdeka curriculum.